Discovery of Mycobacterium tuberculosis CYP121 new inhibitor via structure-based drug repurposing - El Moudaka, Tarek; Murugan, Priya; Abdul Rahman, Mohd Basyaruddin; Tejo, Bimo Ario (Universiti Putra Malaysia Press, 2022)
Tuberculosis (TB) remains a serious threat to human health with the advent of multi-drug resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB). The urge to find novel drugs to deal with the appearance of drug-resistant TB and its variants is highly needed. This study aims to find new CYP121 inhibitors by screening 8,773 compounds from the drug repositioning database RepoDB. The selection of CYP121 potential inhibitors was based on two criteria: the new inhibitor should bind to CYP121 with higher affinity than its original ligand and interact with catalytically important residues for the function of CYP121. The ligands were docked onto CYP121 using AutoDock Vina, and the molecular dynamics simulation of the selected ligand was conducted using YASARA Structure. We found that antrafenine, an anti-inflammatory and analgesic agent with high CYP inhibitory promiscuity, was bound to CYP121 with a binding affinity of -12.6 kcal/mol and interacted with important residues at the CYP121 binding site. Molecular dynamics analysis of CYP121 bound to the original ligand and antrafenine showed that both ligands affected the dynamics of residues located distantly from the active site. Antrafenine caused more structural changes to CYP121 than the original ligand, as indicated by a significantly higher number of affected residues and rigid body movements caused by the binding of antrafenine to CYP121.